The Role of the Vice President in the Republic of Indonesia's Administrative System (Post Amendment to the 1945 Constitution) - Trio Handoyo; Saefudin (Institute Of computer Science (IOCS), 2022)
The purpose of this study was to find out and analyze the role of the Vice President in the state administration of the Republic of Indonesia after the amendments to the 1945 Constitution. The data collection method used in this study was a literature study. The approach method used in this study is a normative juridical approach, namely research based on data obtained from laws and regulations. The data analysis method used is descriptive qualitative. The results of the research are as follows: (1) in the 1945 Constitution before the amendment, the role of the Vice President could be considered as a